Le renvoi et la classification des infractions d’agression sexuelle - Roberts, Julian; Pires, Alvaro (Criminologie, 1992)
This study is a theoretical and empirical analysis of the new tripartite structure of sexual offences created by the Criminal code reform of 1983 in Canada (Bill C-127). The authors analyze the reform proposals advanced by the Law Reform Commission as well as the data on reports of sexual assault in Quebec and Canada as a whole. In addition, the authors explore the actual classification practices of the criminal justice system and some of the "new " symbolic effects of the legislation.